Evaluation on Efficacy of Piper nigrum as a bio-pesticide against Sitophilus zeamais - Choden, Sangay; Yangchen, Ugyen; Tenzin, Jigme (Asian Health, Science and Technology Reports, 2020)
Seed of black pepper, Piper nigrum L, was evaluated for its toxicity, antifeedant and repellency properties against adult Sitophilus zeamais in the laboratory. The bioassays for oil extract and powder of piper seed tested separately in a completely randomized design (CRD) by incorporating different concentrations into the maize with the pest. Analysis of variance (ANOVA) and means of different treatments compared at significance level (p ≤ .05) using Bonferroni pair wise Post Hoc Test for data analysis. Different concentrations showed significantly different effect in all the bioassay tests. Mortality percentage of S. zeamais using oil extract at 96 hours of exposure time was 100±.0% for both 5% and 10% (w/v) concentrations. The mean weight loss percent of maize was minimum (0.13±.12%) when treated with 10% (w/v) oil extract. Maximum (84.0±17.4%) mean repellency percent at concentration 10% (w/v) indicating high repellency and minimum (20.4±17.3%) at concentration 2.5% (w/v) indicating low repellency. Powder of P. nigrum seed exhibits 100% mortality of S. zeamais after 192 hours when treated with concentration 1.5 g/kg of maize whereas for 0.5 g/kg required 216 hours. In case of antifeedant property, significantly lower weight loss of 0.46±.30% was recorded in maize treated with 1.5 g/kg maize compared to 2.92±.38% weight loss in control. Therefore, efficiency of pesticide properties in oil extract of Piper nigrum L at 10% (w/v) concentration performed better than the powder form.